Pectin Extraction from Kepok Banana Peel (Musa acuminata × balbisiana); Case Study on Procedure of Pre-Treatment Process - Silvia Oktavia Nur Yudiastuti; Ismi Lailia Anggita (Agriprima : Journal of Applied Agricultural Sciences, 2023)
The extraction of pectin from banana peels is one way to increase the use value of banana peel waste. The extraction method applied is solid-liquid extraction using an acid solvent. The purpose of this study was to determine the effect of pre-treatment, the type and concentration of solvent as well as the optimum time and substrate concentration, on the resulting yield. This research was conducted experimentally with the OFAT (One Factor at a Time) method. The results showed that the best solvent was 0.5N sulfuric acid with a substrate concentration of 10% for 80 minutes, resulting yield of 10.02%.